A Comparative Study on Extraction, Purification and Characterization of Amylase Enzyme from Aspergillus niger and Aspergillus awamori - G, Swaroop; Karakaraddi, Dr Ashwini; Kumar G, Vinod (International Journal of Biological Research, 2013)
Amylase is an enzyme, which is produced by the microorganisms, which has many applications in today’s market. Amylase is required in digestion of carbohydrates into smaller units and eventually converting them into even smaller units such as glucose. It is also involved in inflammatory reaction, such as those caused by the release of histamine and similar substances. A number of digestive enzymes including amylase are required to produce fructose in large quantities. Objective of our research is to study the comparative production of amylase enzyme from both the fungal strains of Aspergillus niger and Aspergillus awamori which are used as the digestive enzymes in baby foods. In this study we have investigated the level of amylase produced by the each Aspergillus strain, isolation and characterization will be discussed in detail.